Food for Thought: Nurture and Nature in "The Giver" - Ramos, Iolanda (Cadernos de Literatura Comparada (teste), 2017)
Lois Lowry's novel The Giver is usually addressed as a utopian/dystopian narrative. This essay adds a Food Studies framework both to the context of feeding the community and the reception of memories by the young protagonist in the story. The ontological ambiguities found in the novel allow the contemporary readers (and filmgoers) to raise questions about the importance of the choices and compromises we make, as well as to acknowledge that there are always consequences to our actions.